Surface tension gradients: feasible model for gliding motility of Myxococcus xanthus. - Keller, K H (1983)
We propose that surface tension is the driving force for the gliding motility of Myxococcus xanthus. Our model requires that the cell be able to excrete surfactant in a polar and reversible fashion. We present calculations that (i) estimate the surface tension difference across a cell necessary to move the cell at the observed rate, which is less than 10(-5) dyn/cm, an extremely small value; (ii) estimate the rate of surfactant excretion necessary to produce the required surface tension difference, a rate that we conclude to be metabolically reasonable; (iii) predict the behavior of cells moving in close apposition to each other, and show that the model is consistent with observed behavior; and (iv) predict the behavior of cells moving in dense swarms. In an accompanying paper we present experimental evidence to support the surface tension model.